Globalisasi dan Demokrasi di Rusia: Suatu Tantangan dan Peluang - Permatasari, Diah Ayu (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2017)
Globalization has brought many changes in the world and has huge implications for the economy, politics, and socio-culture. The break up of the Soviet Union in 1991 is one of the historical events caused by globalization and transformed into what it is Russia today. Russia tried to adapt towards globalization by following it national historical pattern, and not following the pattern that has been used by the Western countries. For the West, the transition democracy process in Russia is incomplete, but from the Russian point of view, it is a democracy with a distinction pattern or “the Russian way” that is different from what is practiced by the West. For that reason, this essay tried to look at the Russian political and economic policy to handle the strong current of globalization and democracy.